Sociological Explanation of Fear of Crime in Public Spaces Case Study Mashhad - Rezvani, Mahdie (2017)
Fear of crime is an especially a problem that has troubled the urban communities, affected the urban dissatisfaction and many factors in the city have created and intensified it. Fear of crime is of important issues which reduces access to public places and restricts interaction with these places. The research method is surveying and the information collection technique is through questionnaire. Probable span sampling (PPS) method is used. Sample population was 2000 households which were selected randomly in five categorical clusters from Mashhad city. In this research we try In addition to investigation social factors, it has been tried in the research that spatial components affecting fear of crime in public places inside and outside the neighborhoods is considered.Comment: 25 pages, 3 figures, 12 table